Correlation study of organizational activity on student resilience at the Faculty of Medicine, Udayana University: Studi korelasi keaktifan berorganisasi terhadap resiliensi mahasiswa Fakultas Kedokteran Universitas Udayana - Ni Made Ari Suartini,; Ni Made Swasti Wulanyani, (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
Students face difficulties because they must learn and develop by joining organizations. Therefore, resilience is needed. This study aims to determine the role of organizational activity on the resilience of students of the Medical Faculty at Udayana University. The research subjects were 150 organizational functionary students at the Medical Faculty, Udayana University. The measurement uses the Organizational Activeness and Resilience Scale constructed by researchers. The results show that organizational activity plays a role and contributes 39.1% to increasing resilience. Being active in an organization develops flexibility, creativity and becomes a source of social support that increases resilience.